Evaluating Company's Performance Using Multiple Discriminant Analysis: The Case Of Shariah Compliance Companies - Nuradli Ridzwan Shah Mohd Dali; Hamdi Hakeim Mudasir; Suhaila Abdul Hamid (Inderscience Publisher Ltd., 2024)
Non-Indexed Publication